(3CQHYhf MOjKkGs - (3eMeO Hf CHj HcQs ((3eMeO YKeGf s)
(3ChdgG (B:s
(3aLeY GdYHO CQHYjf MOjKkG HGdCSGfjO GdeJUdI Edi GdfHi Udi Gddg Ydjg GdSdGe s
(3BNQgG (B:s
(3bGdJ GdUMGHI jG QShd Gddg gd HYOfG CMO jchf CaVd efG bGd fYe bGdhG (B: (3agd jQhfc bGd GdfHi Ydjg GdSdGe dG hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3hGdeNWhW Je WHYg ai cJGH eWHhYs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
Keywords: (3GdMOjK h GdeUWdMs